2004
DOI: 10.1074/jbc.c400313200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metastasis-related Genes in a Mouse Model Using a Library of Randomized Ribozymes

Abstract: Libraries of randomized ribozymes have considerable potential as tools for the identification of functional genes critically involved in a biological phenotype of interest in vitro.We have used a ribozyme library in an in vivo mouse model to identify genes related to metastasis. We injected weakly metastatic melanoma cells that had been treated with the library intravenously into mice. We then isolated ribozymes that accelerated metastasis from pulmonary tumors that had developed from metastasizing cells. As c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 24 publications
(30 reference statements)
1
39
1
Order By: Relevance
“…Considered collectively, these studies show that Ca 2ϩ entry supports the migration and invasion by melanoma cells. However, in 2004, an unbiased screen for metastasis-related genes in an invasive melanoma model revealed STIM1 as a repressor of metastasis (16). This apparent inconsistency with current thinking is supported by the surprising findings of the current study, in which we examined the expression and function of STIM1 and Orai1 in a series of melanoma cell lines exhibiting marked differences in Wnt5A expression with corresponding differences in invasive character (17,18).…”
mentioning
confidence: 38%
“…Considered collectively, these studies show that Ca 2ϩ entry supports the migration and invasion by melanoma cells. However, in 2004, an unbiased screen for metastasis-related genes in an invasive melanoma model revealed STIM1 as a repressor of metastasis (16). This apparent inconsistency with current thinking is supported by the surprising findings of the current study, in which we examined the expression and function of STIM1 and Orai1 in a series of melanoma cell lines exhibiting marked differences in Wnt5A expression with corresponding differences in invasive character (17,18).…”
mentioning
confidence: 38%
“…Using rhabdomyosarcoma cells in vitro and rhabdoid tumors in vivo, Stim1 was shown to inhibit the growth of tumor cells [32] and be expressed in many human primary and transformed cell lines [30]. The selective suppression of stim1 mRNA brought about rhabdomiasarcoma tumorigenesis [32] and with the application of randomized ribozymes to metastasizing cells, Stim1 mRNA broke down to promote the pulmonary metastasis of B16F0 cells [33]. Stim1 and Stim2 have recently been shown essential to Ca 2+ -store-depletion-mediated Ca 2+ -influx or storeoperated Ca 2+ (SOC) influx, based on data obtained using siRNA techniques [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…STIM1 mRNA is widely expressed in different human tissues, and strongly presented in lymphoid and myeloid cells (9). STIM1 knockdown accelerates the cell motility of melanoma cells and is defined as an antimetastasis gene (12). However, Yang et al (13) demonstrated that STIM1 or Orai1 silencing inhibits the migration and metastasis of breast cancer cells by suppressing focal adhesion turnover.…”
Section: +mentioning
confidence: 99%